Evaluating effect of rejuvenators on high RAP mixtures through laboratory performance tests and construction of field test sections. (18th July 2022) - Moon, Byungkyu; "David" Lee, Hosin; Ledtje, Paul; Williams, Chris
Highlights: Based on the SCB-IFIT test results, for both 34% and 45% RAP mixtures, rejuvenators were effective in lowering cracking potential. Based on a condition survey, rejuvenators were effective in delaying an initiation of cracking. High RAP mixtures with 34% and 45% RAP materials were successfully constructed in Iowa while exceeding Iowa DOT's field density requirement of 93%. Continuous PG grading rejuvenated asphalt binders were performed where Tufftrek was more effective in lowering both critical high and low temperatures than Invigorate. Based on HWT test results, both rejuvenators more effective in lowering the moisture susceptibility than a softer binder and Tufftrek was more effective in lowering a rut depth than Invigorate. Abstract: Although thirty-one US states utilize 20% recycled asphalt pavement (RAP) or greater in asphalt pavements, Iowa limits the usage of RAP to 20%, and 30% with a softer binder in the surface layer. Because high RAP mixtures can cause asphalt mixtures to stiffen due to the hardening effect of the aged binder, rejuvenators should be used to improve the cracking resistance of high RAP mixtures. Due to increasing demand for sustainable, and environmentally materials, two bio-based rejuvenators, Invigorate and Tufftreck, were considered for this study. To evaluate effect of rejuvenators on high RAP mixtures, field test sections were constructed in Cerro Gordo County, Iowa, 2020. The field test consists of six different sections with two rejuvenators and three different RAP contents of 22%, 34% and 45%. Performance grading (PG) of asphalt with rejuvenators adopted for the field test sections lowered both high and low temperatures of the virgin asphalt. Based on the eight cores for each test section, all six test sections with or without rejuvenators exhibited field densities between 93.6% and 95.2%, exceeding the minimum requirement of 93%. First, loose field samples were compacted at the laboratory for Hamburg wheel tracking test, semi-circular bending test, and disc-shaped compact tension test. Second, the laboratory test results were analyzed to determine if rejuvenators were effective in mitigating rutting, moisture damage and cracking. Based on the analysis of limited laboratory test results, Tufftrek was effective in lowering rutting and moisture damage whereas, for minimizing cracking, using a soft binder was most effective. Third, a condition survey on test sections was performed in one year after construction. Based on a condition survey of six test sections, no rutting was observed from all test sections, but some low-severity cracks were observed in sections without rejuvenators. Based on the limited condition survey results, it can be concluded that rejuvenators were effective in delaying the initiation of cracking.